Pengaruh Motivasi dan Persepsi Pegawai tentang Kepemimpinan Kepala Sekolah terhadap Kinerja Guru SMP Negeri 21 Surakarta - Indriastuti Kusuma Mardiyani; Kismartini Kismartini; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The level of education that both can be meant that human resources in a country can be classed quality. The problem about the quality of education has long been questioned of various perspective and a way of seeing. One attention namely against low the quality of education in Indonesia. With low quality in indonesia this means the purpose of our country cannot be achieved with good. This is related to the professionalism of teachers. This research was conducted on SMPN 21 Surakarta. The purpose of this research is to know the influence of motivation and employee perceptions about the principal’s leadership on the teacher performance on SMPN 21 surakarta. But there are things that can weaken and hinder the performance of the job less challenging, the motive to get attention, the least responsibility of leadership and leadership of humanitarian relations with employees. The research method used is a quantitative research eksplanatori. Data obtained in this study using questionnaire. Analysis of data used is a correlation coefficient kendall and coefficients concordance kendall.Data processing using program spss 16.0. The research by using program spss this can be known that motivation ( x1 ) against the employee performance ( y ) with a correlation coefficient kendall know of 0.487 with figures probability 0.006 and the value of KD 23,71%; There is an influence that perception employees about leadership ( x2 ) against the employee performance ( y ) with a correlation coefficient kendall know as much as 0.395 with a probability 0.026 and the value of KD 15,60%; while the employee performance ( y ) with a correlation coefficient kendall know as much as 0.487 with a probability 0.006; Determination to the coefficient ( KD ) indicated on coefficients kendall’s W of 0.290 and the value of the coefficient of determination (KD) by 8,41% With respect to the existence of things that can undermine performance, then it needs to be done to fix the problems found in the indicator, that is the leadership giving praise and attention to the employees of his work that has been done as often as possible, the Chairman gave the task could be more skills, initiative and creativity so that employees can also develop themselves, the need for the improvement of the relationship between leadership and employees so that chick nearness and familiarity. It takes self awareness of leadership for responsible for everything that happens in the scope of work. With the aim to repair can improve the performance of teachers get better, so education in Surakarta to become better.